Liquid desiccant dehumidification system design and experimental performance testing - Gu, Haoran (2019)
In this fast-growing society, people are increasingly demanding quality of life. Among them, indoor air quality, especially indoor air humidity, has been paid attention. However, in the conventional system, the dehumidification function and the temperature control function cannot fully achieve the expected goals. Moreover, when the system works, the energy consumption is very high, resulting in a large amount of energy waste. Therefore, the development of a multi-functional and low energy consumption air conditioning system has been the development goal of the current control industry.